A copper nanoparticle material and its preparation and application

By catalyzing furfural or furfurfurol by using smooth non-porous nanocopper materials prepared by copper-aluminum alloy, the problem of expensive precious metal catalysts and environmental pollution is solved, and the efficient and low-cost preparation of pentyl glycol is achieved, which is suitable for a variety of industrial applications.

CN115446301BActive Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110556710.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-21
Publication Date
2025-01-14
Estimated Expiration
2041-05-21

AI Technical Summary

Technical Problem

In the prior art, precious metal catalysts are expensive and have environmental pollution problems. There is no document that non-precious metal catalysts can effectively catalyze the conversion of furfural to pentylene glycol. The protective agents of nanocopper materials affect the catalytic performance.

Method used

Using copper-aluminum alloy as raw material, the aluminum atoms in the alloy are removed by dropping the alkaline solution to prepare smooth and non-porous nanocopper materials, which are used to catalyze the hydrogenation of furfural or furfurfurol to prepare pentyl glycol, avoiding the use of protective agents, and realizing the Recycling of catalysts and low cost.

Benefits of technology

The efficient catalytic conversion of furfural or furfurfural alcohol to pentyl glycol is achieved, reducing catalyst costs, avoiding environmental pollution, and the size of nano-copper materials is easy to regulate, and is suitable for the petroleum lubricant and electronic devices industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115446301B_ABST
    Figure CN115446301B_ABST
Patent Text Reader

Abstract

The present invention provides a nano copper material containing aluminum hydroxide to catalyze the liquid phase hydrogenation of furfural or furfuryl alcohol to pentanediol. The nano copper material carries a certain amount of aluminum hydroxide, and copper aluminum alloy is used as a raw material in the preparation process, and the particle size of the copper aluminum alloy used does not exceed 500 microns. Alkaline solution is added dropwise to remove aluminum atoms in the alloy, and then residual aluminum, sodium salt and other compounds are washed with water until the washing liquid is neutral. In the furfural or furfuryl alcohol liquid phase hydrogenation system, the nano copper material is used as a catalyst, and the reaction is carried out at a certain temperature and hydrogen pressure to obtain a pentanediol product accompanied by methylfuran. In the invention, a non-precious metal copper material is used as a catalyst, which is low in price and can be recycled. The catalyst preparation process is simple, does not require a template agent or a protective agent, and the size of the obtained nano copper material is easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano copper material catalyzing the liquid phase hydrogenation of furfural or furfuryl alcohol to produce pentanediol. Background Art

[0002] 1,2-Pentanediol and 1,5-Pentanediol are widely used organic chemicals. Among them, 1,2-Pentanediol is an important intermediate of the fungicide propiconazole and an excellent moisturizer. It is used in various skin care products such as skin creams, eye creams, skin lotions, baby care products, sunscreen products, etc. It also has an antiseptic effect and can be used to formulate preservative-free products. 1,5-Pentanediol is an important chemical precursor, used as a solvent for cutting oils, special detergents, latex paints, solvents or wetting agents for inks, and is also used to manufacture plasticizers, brake fluids, alkyd resins, polyurethane resins, etc.

[0003] Furfural can be obtained by acid hydrolysis of hemicellulose in renewable resource lignocellulose, and pentanediol can be obtained by hydrogenation and other processes. In recent years, the route of preparing pentanediol using biomass-based compounds furfural and its derivative furfuryl alcohol as raw materials has attracted widespread attention. At present, in the reaction of furfural or furfuryl alcohol to pentanediol, the catalyst is mostly a precious metal catalyst such as Pt, Pd, Ru, etc. (Chem. Rev. 2018, 118, 11023-11117, Catalysts 2019, 9, 796, CN201210354918.7), and precious metals are expensive. It is of great significance to develop efficient catalysts for the conversion of non-precious metal furfuryl alcohol and furfuryl alcohol to pentanediol.

[0004] Adkins et al. reported that copper chromite was used as a catalyst to catalyze the hydrogenolysis of furfuryl alcohol to produce pentanediol at 175 degrees and 10-15 MPa (J.Am.Chem.Soc., 1931, 53, 1091-1095). However, the catalyst contained toxic element Cr, which would cause environmental pollution and other problems. Liu Hailong et al. prepared a supported copper catalyst with alumina, Mg3AlO 4.5 , LaCoO3, is used to catalyze the conversion of furan compounds to pentanediol, but the only reported reaction substrate is furfuryl alcohol (Chinese Journal of Catalysis 39 (2018) 1711–1723; Chinese Journal of Catalysis 37 (2016) 700–710; Catal. Sci. Technol., 2016, 6, 668). There is currently no literature report on the conversion of furfural to pentanediol catalyzed by non-precious metal catalysts.

[0005] Nano copper materials are inexpensive and can be widely used in catalysis, microelectronic device manufacturing, petroleum lubricants, pharmaceutical industry, etc., and have great industrial application value. At present, there are mainly the following methods for preparing nano copper: 1. Wet chemical synthesis (Chinese patents 201910318866.X, 201810982155.8, 200710120644.4); 2. Biosynthesis; 3. Electrochemical synthesis (Chinese patent 201110009443.3); 4. Atomic layer deposition; 5. Photochemical synthesis; 6. Supercritical method; 7. Microwave-assisted method, etc. (Chemical Methodologies 2019, 3, 457-480). Among them, wet chemical synthesis of nano copper is simple to operate, low in cost, and has the characteristics of easy regulation of particle size. In this method, a reducing agent (sodium borohydride, hydrazine hydrate, etc.) is used to reduce copper ions to zero-valent copper, and a protective agent (compounds such as vitamin C, hexadecyl trimethyl ammonium, sodium dodecyl sulfate, etc.) is used to protect nano copper to prevent nano copper from agglomeration and oxidation (Nanoscale Res. Lett. 2009, 4, 465). However, the protective agent remaining in the nano copper material will affect the scope of its application. For example, the presence of a protective agent will affect the adsorption and activation of the reaction substrate on the catalyst copper atom, thereby affecting its catalytic performance.

[0006] According to the literature and patents (CN102603681A, Applied Catalysis A: General 509, 2016, 153-160), a skeletal porous copper can be obtained after eluting the copper-aluminum alloy with alkaline solution, and has good reaction performance in the reaction of furfural hydrogenation to furfuryl alcohol. Even under the same reaction conditions, no furfuryl alcohol hydrogenolysis product pentanediol is generated.

[0007] In the present invention, copper-aluminum alloy is used as raw material, the alloy particle size used is small (not higher than 500 microns) and a sieve with a certain mesh number is used to screen out copper-aluminum alloy of different particle sizes to ensure the relative uniformity of particle size, alkaline solution is slowly dripped to remove part of the aluminum atoms in the alloy, and then residual aluminum, sodium salt and other compounds are washed with water until the washing liquid is neutral, and a smooth non-porous structure nano copper material can be obtained, and a nano copper material with a size less than 200nm can be obtained by controlling the alkali liquid drop acceleration rate, and a certain amount of aluminum hydroxide is carried in the nano copper material, which can be used for furfural or furfuryl alcohol hydrogenation to produce pentanediol with higher added value, and the nano copper material can also be applied to petroleum lubricants, electronic device industries, etc. In the present invention, non-precious metal copper material is used as a catalyst to catalyze the reaction of furfural or furfuryl alcohol hydrogenation to produce pentanediol, which is cheap and the catalyst can be recycled. And the nano copper material preparation method is simple, does not need to use protective agents such as template agents and surfactants, and the size of nano particles can be regulated by adjusting the conditions of preparation. Summary of the invention

[0008] The invention aims to provide a copper nanoparticle material containing aluminum hydroxide for catalyzing the liquid phase hydrogenation of furfural or furfuryl alcohol to produce pentanediol.

[0009] The copper nanoparticles are smooth and non-porous, with a size of 10-200nm, preferably 50-100nm. The average particle size is 70nm.

[0010] The amount of aluminum hydroxide contained is 0.1%-30wt% of the nano copper particle material, preferably 1%-10wt%.

[0011] In the process of preparing the nano copper material, copper-aluminum alloy is used as raw material, and the particle size of the copper-aluminum alloy used is 5-500 microns, preferably 10-200 microns, and more preferably 10-150; the mass fraction of Al in the copper-aluminum alloy is 20%-80%, preferably 25%-60%, and more preferably 35-50%;

[0012] At a certain temperature, an alkaline solution is added dropwise to an aqueous solution containing copper-aluminum alloy particles to partially remove some aluminum metal atoms in the alloy to obtain the target product.

[0013] The alkaline solution is a strong alkaline solution; one or more of sodium hydroxide, potassium hydroxide, sodium alcoholate, potassium alcoholate, etc.; preferably one or both of sodium hydroxide and potassium hydroxide.

[0014] The mass concentration of the alkaline solution is 1%-80%, preferably 10%-60%, and more preferably 15%-50%.

[0015] The molar amount of the alkaline compound added is 2-10 times the molar amount of aluminum in the copper-aluminum alloy;

[0016] Preferably, the molar amount of the alkaline compound added is 3-6 times the molar amount of aluminum in the copper-aluminum alloy.

[0017] The amount of water is 0.1-60 times the mass of the copper-aluminum alloy, preferably 1-30 times, and more preferably 3-8 times.

[0018] The mass of alkaline compounds added to the copper-aluminum alloy per minute is less than twice the mass of the copper-aluminum alloy; preferably, the amount of alkaline compounds added to the copper-aluminum alloy per minute is less than the mass of the copper-aluminum alloy, and more preferably, the mass of alkaline compounds added to the copper-aluminum alloy per minute is 0.05%-50% of the mass of the copper-aluminum alloy.

[0019] The reaction temperature is 10-90 degrees, preferably 40-70 degrees.

[0020] The reaction time after adding the alkaline solution is 0-180 min, preferably 5-120 min, more preferably 5-60 min;

[0021] After the reaction, the solid product is washed with water until the washing liquid is neutral to obtain the desired product.

[0022] The copper nanoparticle material can be used to catalyze the liquid phase hydrogenation of furfural and / or furfuryl alcohol to produce pentanediol.

[0023] Weighing nano copper particles to catalyze the liquid phase hydrogenation reaction of furfural or furfuryl alcohol, and carrying out the reaction at a certain temperature and hydrogen pressure, pentanediol can be obtained, accompanied by the generation of methyl furan;

[0024] The temperature of the hydrogenation reaction is 130-250 degrees, preferably 150-200 degrees, more preferably 160-190;

[0025] The hydrogen pressure of the hydrogenation reaction is 1-10Mpa, preferably 4-8Mpa;

[0026] The hydrogenation reaction time is 0.5-24h, preferably 0.5-13h, more preferably 2-8h.

[0027] In the invention, non-precious copper material is used as a catalyst, which is low in price and can be recycled. The catalyst preparation process is simple, does not require a template agent or a protective agent, and the size of the obtained nano copper material is easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is one of the high-resolution scanning electron microscope images of Example 1;

[0029] Figure 2 This is the second high-resolution scanning electron microscope image of Example 1;

[0030] Figure 3 This is the third high-resolution scanning electron microscope image of Example 1;

[0031] Figure 4 This is a high-resolution transmission electron microscope image of Example 1. DETAILED DESCRIPTION

[0032] The following is a further detailed description of the preparation process of nano copper materials. The protection content of this patent is not limited to the specific implementation method, but is limited by the claims.

[0033] Example 1

[0034] Weigh 10g of copper-aluminum alloy (30%wt Al, 45um<particle size<105um, morphology as Figure 1), 50ml of water into a beaker, heat to 50 degrees, prepare 30% NaOH solution, add NaOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 4.7 times the molar amount of Al) into the beaker, control the time to 80min (the mass of NaOH added per minute is 2.6% of the mass of the copper-aluminum alloy), stir continuously, and react for 0.5h after the addition is completed. After the reaction is completed, wash the obtained nano-copper material with water until the washing liquid is neutral. The particle size of the obtained copper nano-material is 30-100nm (average particle size 60nm), and the aluminum hydroxide content is 2wt% by ion chromatography analysis, and the smooth non-porous structure (morphology, particle size such as Figure 2 , 3, 4).

[0035] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, and react for 6 hours. The obtained furfural conversion rate is 100%, the yield of methyl furan is 32%, and the yield of pentanediol is 30%. Centrifuge after the reaction, pour out the liquid to recover the catalyst, add 10 ml of isopropanol and centrifuge again, pour out the liquid to wash away the reactants, products, etc. remaining in the catalyst, and wash the catalyst 5 times in total. Repeat the above furfural hydrogenation reaction, the obtained furfural conversion rate is 100%, the yield of methyl furan is 31%, and the yield of pentanediol is 30%.

[0036] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 160 degrees, react for 13 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 34%, and the pentanediol yield is 32%.

[0037] Furfuryl alcohol hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfuryl alcohol, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfuryl alcohol conversion rate is 96%, the methylfuran yield is 38%, and the pentanediol yield is 36%.

[0038] Comparative Example 1

[0039] 80 mg of the copper nanomaterial prepared in Example 1 (size 30-100 nm, aluminum hydroxide content 2 wt%), 500 mg of furfural, and 2 ml of isopropanol were weighed into a reactor, filled with 4.5 MPa H2, and the temperature in the reactor was controlled at 110 degrees. The reaction was carried out for 3 hours, and the conversion rate of furfuryl alcohol was 99%, the yield of furfuryl alcohol was 99%, and no pentanediol was produced.

[0040] Comparative Example 2

[0041] About 100 mg of copper nanomaterial (particle size 60-100 nm, excluding aluminum hydroxide), 500 mg of furfuryl alcohol, and 2 ml of isopropanol were weighed into a reactor, filled with 4.5 MPa H2, and the temperature in the reactor was controlled at 170 degrees. The reaction was carried out for 6 hours, and the conversion rate of furfuryl alcohol was 6.8%, the yield of methylfuran was about 5.1%, and no pentanediol was generated.

[0042] Example 2

[0043] Weigh 10g copper-aluminum alloy (30%wt Al, 5um<particle size<45um) and 50ml water into a beaker, heat to 50 degrees, prepare 30% NaOH solution, add NaOH solution (70ml, the molar amount of sodium hydroxide is 4.7 times the molar amount of Al) dropwise into the beaker, control the time to 400min (the mass of NaOH added dropwise per minute is 5.2% of the mass of the copper-aluminum alloy), stir continuously, and react for 0.5h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-80nm (average particle size 50nm), smooth and non-porous structure, and ion chromatography analysis shows that the aluminum hydroxide content is 3wt%.

[0044] Furfural hydrogenation: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 150 degrees, react for 13 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 23%, and the pentanediol yield is 27%.

[0045] Example 3

[0046] Weigh 10g copper-aluminum alloy (30%wt Al, 75um<particle size<105um) and 50ml water into a beaker, heat to 50 degrees, prepare 30% NaOH solution, add NaOH solution (140ml, the molar amount of sodium hydroxide is 9.5 times the molar amount of Al) dropwise into the beaker, control the time to 600min (the mass of NaOH added per minute is 0.7% of the mass of the copper-aluminum alloy), stir continuously, and react for 0.1h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 50-180nm (average particle size 100nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 2wt%.

[0047] Furfural hydrogenation: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 5 MPa H2, control the temperature in the reactor to 200 degrees, react for 4.5 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 38%, and the pentanediol yield is 22%.

[0048] Example 4

[0049] Weigh 5g copper-aluminum alloy (30%wt Al, 105um<particle size<200um) and 30ml water into a beaker, heat to 50 degrees, prepare 30% NaOH solution, add NaOH solution (70ml, the molar amount of sodium hydroxide is 9.5 times the molar amount of Al) dropwise into the beaker, control the time for 20min (the mass of NaOH added per minute is 21% of the mass of the copper-aluminum alloy), stir continuously, and react for 1h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 100-200nm (average particle size 150nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 4wt%.

[0050] Furfural hydrogenation: weigh about 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 160 degrees, react for 13.3 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is about 33%, and the pentanediol yield is about 35%.

[0051] Example 5.

[0052] Weigh 10g copper-aluminum alloy (60%wt Al, 45um<particle size<75um) and 30ml water into a beaker, heat to 50 degrees, prepare 30% NaOH solution, add NaOH solution dropwise (about 140ml, the molar amount of sodium hydroxide is 4.7 times the molar amount of Al) into the beaker, control the time to 160min (the mass of NaOH added per minute is 5.2% of the mass of the copper-aluminum alloy), stir continuously, and react for 0.5h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-90nm (average particle size 50nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 6wt%.

[0053] Furfuryl alcohol hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfuryl alcohol, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 150 degrees, react for 2 hours, and the obtained furfuryl alcohol conversion rate is 40%, methylfuran selectivity is 14%, and pentanediol selectivity is 47%.

[0054] Example 6.

[0055] Weigh 10g copper-aluminum alloy (30%wt Al, 45um<particle size<75um), 50ml water into a beaker, heat to 50 degrees, prepare 30% KOH solution, add KOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 4.7 times the molar amount of Al) into the beaker, control the time for 80min (the mass of NaOH added dropwise per minute is 2.6% of the mass of the copper-aluminum alloy), stir continuously, and react for 0.5h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-100nm (average particle size 60nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 10wt%.

[0056] Furfural hydrogenation: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 6 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 30%, and the pentanediol yield is 35%.

[0057] Example 7.

[0058] Weigh 10g copper-aluminum alloy (30%wt Al, 45um<particle size<75um) and 50ml water into a beaker, heat to 90 degrees, prepare 30% NaOH solution, add NaOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 4.7 times the molar amount of Al) into the beaker, control the time to 80min (the mass of NaOH added dropwise per minute is 2.6% of the mass of the copper-aluminum alloy), stir continuously, and react for 20min after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 80-200nm (average particle size 120nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 3wt%.

[0059] Furfural hydrogenation: weigh about 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of n-propanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is about 30%, and the pentanediol yield is about 34%.

[0060] Example 8.

[0061] Weigh 10g copper-aluminum alloy (50%wt Al, 45um<particle size<75um) and 50ml water into a beaker, heat to 30 degrees, prepare 30% NaOH solution, add NaOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 2.8 times the molar amount of Al) into the beaker, control the time to 500min (the mass of NaOH added per minute is 0.4% of the mass of the copper-aluminum alloy), stir continuously, and react for 5min after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is about 30-100nm (average particle size 60nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 10wt%.

[0062] Furfural hydrogenation: Weigh 50 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 6 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 37%, and the pentanediol yield is 30%.

[0063] Example 9.

[0064] Weigh 10g copper-aluminum alloy (50%wt Al, 45um<particle size<75um) and 50ml water into a beaker, heat to 30 degrees, prepare 60% NaOH solution, add NaOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 5.6 times the molar amount of Al) into the beaker, control the time to 100min (the mass of NaOH added per minute is 4.2% of the mass of the copper-aluminum alloy), stir continuously, and react for 3h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is about 60-180nm (average particle size 100nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 7wt%.

[0065] Furfural hydrogenation: Weigh 50 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 6 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 30%, and the pentanediol yield is 31%.

[0066] Example 10.

[0067] Weigh 10g copper-aluminum alloy (50%wt Al, 45um<particle size<75um) and 5ml water into a beaker, heat to 50 degrees, prepare 10% NaOH solution, add NaOH solution dropwise (about 300ml, the molar amount of sodium hydroxide is 4.1 times the molar amount of Al) into the beaker, control the time to 150min (the mass of NaOH added per minute is 2% of the mass of the copper-aluminum alloy), stir continuously, and react for 3h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-100nm (average particle size 60nm), and the structure is smooth and non-porous. The aluminum hydroxide content is 10wt%.

[0068] Furfuryl alcohol hydrogenation: Weigh 50 mg of the prepared copper nanomaterial, 500 mg of furfuryl alcohol, and 2 ml of isopropanol into a reactor, fill with 6 MPa H2, control the temperature in the reactor to 170 degrees, react for 10 hours, and the obtained furfuryl alcohol conversion rate is 100%, the methylfuran yield is 15%, and the pentanediol yield is 43%.

[0069] Embodiment 11

[0070] Weigh 30g copper-aluminum alloy (30%wt Al, 45um<particle size<105um) and 50ml water into a beaker, heat to 50 degrees, prepare 60% NaOH solution, add NaOH solution dropwise (about 100ml, the molar amount of sodium hydroxide is 4.5 times the molar amount of Al) into the beaker, control the time to 200min (the mass of NaOH added per minute is 3.3% of the mass of the copper-aluminum alloy), stir continuously, and react for 1h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-100nm (average particle size 60nm), and the aluminum hydroxide content is 3wt% according to ion chromatography analysis, and the structure is smooth and non-porous.

[0071] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 32%, and the pentanediol yield is 30%.

[0072] Furfuryl alcohol hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfuryl alcohol, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfuryl alcohol conversion rate is 96%, the methyl furan yield is 35%, and the pentanediol yield is 34%. Furfuryl alcohol hydrogenation reaction: Weigh 100 mg of the prepared copper nanomaterial, 2 g of furfuryl alcohol, and 4 ml of isopropanol into a reactor, fill with 8 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfuryl alcohol conversion rate is 80%, the methyl furan yield is 30%, and the pentanediol yield is 35%.

[0073] Example 12

[0074] Weigh 5g copper-aluminum alloy (30%wt Al, 45um<particle size<105um) and 300ml water into a beaker, heat to 50 degrees, prepare 70% NaOH solution, add NaOH solution (about 100ml, the molar amount of sodium hydroxide is 9.5 times the molar amount of Al) dropwise into the beaker, control the time of 200min (the mass of NaOH added per minute is 7% of the mass of the copper-aluminum alloy), stir continuously, and react for 3h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 30-100nm (average particle size 60nm), and the aluminum hydroxide content is 1wt% according to ion chromatography analysis, and the structure is smooth and non-porous.

[0075] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 34%, and the pentanediol yield is 33%.

[0076] Example 13

[0077] Weigh 10g copper-aluminum alloy (30%wt Al, 45um<particle size<105um) and 1ml water into a beaker, heat to 50 degrees, prepare 10% NaOH solution, add NaOH solution (300ml, the molar amount of sodium hydroxide is 6.8 times the molar amount of Al) dropwise into the beaker, control the time to 100min (the mass of NaOH added per minute is 10% of the mass of the copper-aluminum alloy), stir continuously, and react for 1h after the addition is completed. After the reaction is completed, wash the obtained nano-copper material with water until the washing liquid is neutral. The size of the obtained copper nano-material is 30-100nm (average particle size 60nm), and the aluminum hydroxide content is 1wt% according to ion chromatography analysis, and the structure is smooth and non-porous.

[0078] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 31%, and the pentanediol yield is 30%.

[0079] Embodiment 14

[0080] Weigh 5g copper-aluminum alloy (30%wt Al, 45um<particle size<105um) and 400ml water into a beaker, heat to 50 degrees, prepare 50% NaOH solution, add NaOH solution (100ml, the molar amount of sodium hydroxide is 6.8 times the molar amount of Al) dropwise into the beaker, control the time for 5min (the mass of NaOH added per minute is 2 times the mass of copper-aluminum alloy), stir continuously, and react for 2h after the addition is completed. After the reaction is completed, wash the obtained nano copper material with water until the washing liquid is neutral. The size of the obtained copper nano material is 40-120nm (average particle size 80nm), and the aluminum hydroxide content is 7wt% according to ion chromatography analysis, and the structure is smooth and non-porous.

[0081] Furfural hydrogenation reaction: Weigh 80 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 100%, the methylfuran yield is 33%, and the pentanediol yield is 32%.

[0082] Comparative Example 3:

[0083] Weigh 10g copper-aluminum alloy (50%wt Al, 45um<particle diameter<75um), 50ml of water in a large beaker, heat to 50 degrees, configure mass concentration is 30% NaOH solution, instantly pour NaOH solution (about 60ml) in the large beaker, constantly stir for 3h. Wash the obtained nano copper material with water after finishing until the washing liquid is neutral, and obtain the copper material particle diameter of 500 nanometers-1 micron. Furfural hydrogenation: weigh prepared copper nano material 50mg, furfural 500mg, isopropyl alcohol 2ml in a reactor, charge 4.5MpaH2, control the temperature in the reactor 170 degrees, react 6h, the obtained furfural conversion rate 90%, no pentanediol generation.

[0084] Comparative Example 4:

[0085] Weigh 10g of copper-aluminum alloy (40%wt Al, 45um<particle size<75um) and 50ml of water into a reactor, prepare a 30% NaOH solution, pour the NaOH solution (about 60ml) into a large beaker, heat to 150 degrees, and stir continuously for 3h. After the reaction, wash the obtained nano-copper material with water until the washing liquid is neutral, and obtain a copper material with a particle size of 500 nanometers to 1 micron.

[0086] Furfural hydrogenation: Weigh 50 mg of the prepared copper nanomaterial, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, and the obtained furfural conversion rate is 80%, and no pentanediol is generated.

[0087] Comparative Example 5:

[0088] Weigh 10g copper-aluminum alloy (40%wt Al, 1mm<particle size<3mm) and 50ml water into a large beaker, heat to 50 degrees, prepare a 30% NaOH solution, add NaOH solution dropwise (about 70ml, the molar amount of sodium hydroxide is 3.5 times the molar amount of Al) into the beaker, control the time to 150min (the mass of NaOH added per minute is 1.4% of the mass of the copper-aluminum alloy), and stir continuously for 2h. After the end, wash the obtained nano copper material with water until the washing liquid is neutral, and obtain a copper material with a particle size of skeleton copper material and a pore size of 10-80 microns.

[0089] Furfural hydrogenation: Weigh 50 mg of the prepared skeleton copper material, 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, the obtained furfural conversion rate is 90%, the furfuryl alcohol yield is 80%, and no pentanediol is generated.

[0090] Comparative Example 6:

[0091] Preparation of loaded copper material by impregnation method: weigh 5g of copper nitrate, dissolve it in 50ml of water, add 5g of carrier (silicon oxide or aluminum oxide), mix well, stir at 60 degrees for 6h, dry at 120 degrees for 12h, calcine at 450 degrees for 4h, and reduce at 250 degrees for 3h to obtain a loaded copper catalyst with a copper nano-ion particle size of 10-50nm.

[0092] Furfural hydrogenation: Weigh 100 mg of the prepared supported copper material (Cu / SiO2 or Cu / Al2O3), 500 mg of furfural, and 2 ml of isopropanol into a reactor, fill with 4.5 MPa H2, control the temperature in the reactor to 170 degrees, react for 6 hours, the obtained furfural conversion rate is 99%, the furfuryl alcohol yield is 90%, and no pentanediol is generated.

Claims

1. An application of copper nanoparticle material containing aluminum hydroxide, characterized in that: The copper nanoparticle material can be used to catalyze the liquid phase hydrogenation of furfural and / or furfuryl alcohol to produce pentanediol; Weighing nano copper particles to catalyze the liquid phase hydrogenation reaction of furfural or furfuryl alcohol, and carrying out the reaction at a certain temperature and hydrogen pressure, pentanediol can be obtained, accompanied by the generation of methyl furan; The temperature of the hydrogenation reaction is 130-250 degrees; The hydrogen pressure of the hydrogenation reaction is 1-10Mpa; The hydrogenation reaction time is 0.5-24h; The copper nanoparticles have a particle size of 10-200 nm; The amount of aluminum hydroxide contained is 0.1%-30wt% of the nano copper particle material; In the process of preparing the nano copper material, a copper-aluminum alloy is used as a raw material, and the particle size of the copper-aluminum alloy used is 5-500 microns; the mass fraction of Al in the copper-aluminum alloy is 20%-80%; At a certain temperature, an alkaline solution is added dropwise to an aqueous solution containing copper-aluminum alloy particles to partially remove some aluminum metal atoms in the alloy to obtain a desired product; The amount of water is 0.1-60 times the mass of the copper-aluminum alloy; The mass of the alkaline compound added to the copper-aluminum alloy per minute is less than twice the mass of the copper-aluminum alloy.

2. The use according to claim 1, characterized in that: The copper nanoparticles have a particle size of 50-100 nm; The amount of aluminum hydroxide contained is 1%-10wt% of the nano copper particle material; In the process of preparing the nano copper material, copper-aluminum alloy is used as raw material, and the particle size of the copper-aluminum alloy used is 10-200 microns; the mass fraction of Al in the copper-aluminum alloy is 25%-60%; The amount of water is 1-30 times the mass of the copper-aluminum alloy; The mass of the alkaline compound added to the copper-aluminum alloy per minute is 0.05%-50% of the mass of the copper-aluminum alloy.

3. The use according to claim 2, characterized in that: In the process of preparing the nano copper material, copper-aluminum alloy is used as raw material, and the particle size of the copper-aluminum alloy used is 10-150 microns; the mass fraction of Al in the copper-aluminum alloy is 35-50%; The amount of water is 3-8 times the mass of the copper-aluminum alloy.

4. The use according to claim 1, characterized in that: The alkaline solution is a strong alkaline solution; The strong base includes one or more of sodium hydroxide, potassium hydroxide, sodium alcoholate and potassium alcoholate.

5. The use according to claim 1 or 4, characterized in that: The mass concentration of the alkaline solution is 1%-80%.

6. The use according to claim 5, characterized in that: The mass concentration of the alkaline solution is 10%-60%.

7. The use according to claim 6, characterized in that: The mass concentration of the alkaline solution is 15%-50%.

8. The use according to claim 1, characterized in that: The molar amount of the alkaline compound added is 2-10 times the molar amount of aluminum in the copper-aluminum alloy.

9. The use according to claim 8, characterized in that: The molar amount of the alkaline compound added is 3-6 times the molar amount of aluminum in the copper-aluminum alloy.

10. The use according to claim 1, characterized in that: The reaction temperature is 10-90 degrees.

11. The use according to claim 10, characterized in that: The reaction temperature is 40-70 degrees.

12. The use according to claim 1, characterized in that: The reaction time after adding the alkaline solution is 5-120 min; After the reaction, the solid product is washed with water until the washing liquid is neutral, thereby obtaining the target product copper nanoparticles, which are non-porous particles with smooth surfaces.

13. The use according to claim 12, characterized in that: The reaction time after adding the alkaline solution is 5-60 minutes.

14. The use of the copper nanoparticle material according to claim 1, characterized in that: The temperature of the hydrogenation reaction is 150-200 degrees; The hydrogen pressure of the hydrogenation reaction is 4-8 Mpa; The hydrogenation reaction time is 0.5-13h.

15. The use of the copper nanoparticle material according to claim 14, characterized in that: The temperature of the hydrogenation reaction is 160-190 degrees; The hydrogenation reaction time is 2-8h.

Citation Information

Patent Citations

  • Preparation method of nano-copper powder

    CN102586800B

  • Method for preparing furfuryl alcohol through furfural liquid-phase catalytic hydrogenation

    CN102603681A